ADMM based demand response management in the future smart grid - Teo, Catherine Meng Jin (2019)
This report is a final year project report, presenting on the research and work done for demand response management in the future smart grid. The aim of this project is to study and develop an Alternating Direction Method of Multipliers (ADMM) based demand response algorithm which will solve an optimization problem in a decentralized manner. Although there are many demand response programs implemented by utilities company, these programs compromise user’s privacy as the user have to report their energy consumptions not only to the utility company, but also all the other users in the grid. ADMM is an algorithm that allows convex optimization problems to be solve by breaking them into smaller part which are easier to handle. Demand response allows consumers to manage their energy consumption that will benefit both the consumer and utilities company, and by implementing ADMM, it ensures that the problem is solved in a parallel and decentralized way, in which guaranteeing user’s privacy and computational stress.